Online Convenience Store System using Multidimensional Data Visualization - Zainal, Nisa Athirah; Saad, Ahmad Fadli (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
The explosion of e-commerce businesses has seen the growth number of the online businesses worldwide. Retailers nowadays are opting with e-commerce platform to manage and monitor the business activities which is considerably convenience such as visualizing the sales data. However, Serbaneka is still using traditional way to store the sales data such as in spreadsheet papers which lead to data loss or misplaced the sales record. The objective of this research is to study the current usage of e-commerce system among hostel students in UiTM Tapah. A preliminary survey was carried out by eight selected hostel students in order to generate a list of criteria based on students' previous experiences with e- commerce systems. The following objective is to develop a web- based convenience store system using multidimensional data visualization for Serbaneka UiTM Tapah. The System Development Life Cycle (SDLC) method is used in the development of Online Convenience Store System for Serbaneka UiTM Tapah. Besides, multidimensional data visualization is used as method in visualizing the sales data of Serbaneka UiTM Tapah. Other than that, this research is to evaluate the usability of the system using Post-Study System Usability Questionnaire (PSSUQ) approach. The PSSUQ evaluation is evaluated by three selected experts. The results of PSSUQ evaluation stated that the experts satisfied with the development of Online Convenience Store System using Multidimensional Data Visualization for Serbaneka UiTM Tapah. This is due to the system's ability to assist retailers Serbaneka UiTM Tapah in managing and monitoring the business activities.